Orphan Care: An Introduction - Jo Daugherty Bailey (Social Work and Society, 2009)
This collection aims to cast light on the social work profession and its care for orphans in middle and low income nations. Four countries are profiled in this work, and the focus in each portrayal is the work done by professionals as well as the socio-political context of this work in the area of care for orphaned children. As will be argued later, both our international perspective and our understanding of the needs and care of orphans around the world are limited in the English language social work literature. This work represents an attempt to address these limitations. I whole-heartedly embrace Watts' urgent call, e"International and comparative social work and social welfare have some catching up to do"¦In order to seek answers, we need to recognize we have much to learn from each other. We have much to learn about how social work is practiced in countries different from our own. We have much to learn about the similarities and the differences in social work in various countries. Our learning about its many facets and expressions can challenge our own interpretations of reality and our own truth claims and move us to new ways of thinking and new ways of understanding" (1997, p. 5).